Socioscientific and epistemic dimensions of support for science: associations with science education and religiosity. Issue 1 (2nd January 2017) - Stewart, Craig O.; McConnell, John R.; Dickerson, Daniel L.
ABSTRACT: This study investigated deference to scientific authority [Brossard, D., & Nisbet, M. C. (2007). Deference to scientific authority among a low information public: Understanding U.S. opinion on agricultural biotechnology. International Journal of Public Opinion Research, 19, 24–52] as it relates to support for science across eight sociocultural domains: the economy, the environment, epistemology, science education for all, public health, race and gender, public policy, and science and religion [Cobern, W. W., & Loving, C. C. (2002). Investigation of preservice elementary teachers' thinking about science. Journal of Research in Science Teaching, 39, 1016–1031]. Results revealed that both increased deference to scientific authority and increased support for science were associated with greater science education and lower religious attendance and revealed two underlying dimensions: an epistemic dimension, combining the deference, epistemology, and science and religion scales, and differing based on religious attendance; and a socioscientific dimension, combining science education for all, economy, environment, and public policy scales, and differing based on science education. In summary, this study suggested that low religious attendance was most strongly associated with support for the value of scientific knowledge and authority, while greater science education was most strongly associated with support for science in schools and society. The effect size for religious attendance was substantially larger than that for science education.